2018
DOI: 10.1007/978-981-13-1666-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Magma Transport Pathways in Large Igneous Provinces: Lessons from Combining Field Observations and Seismic Reflection Data

Abstract: Large Igneous Province (LIP) formation involves the generation, intrusion, and extrusion of significant volumes (typically >1 Mkm 3) of mainly mafic magma and is commonly associated with episodes of mantle plume activity and major plate reconfiguration. Within LIPs, magma transport through Earth's crust over significant vertical (up to tens of kilometres) and lateral (up to thousands of kilometres) distances is facilitated by dyke swarms and sill-complexes. Unravelling how these dyke swarms and sill-complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 175 publications
(376 reference statements)
0
26
0
Order By: Relevance
“…Advancing our understanding of dyke swarm emplacement thus requires a method for imaging their 3D structure in detail (e.g. Magee et al, 2018Magee et al, , 2019Phillips et al, 2018).…”
mentioning
confidence: 99%
“…Advancing our understanding of dyke swarm emplacement thus requires a method for imaging their 3D structure in detail (e.g. Magee et al, 2018Magee et al, , 2019Phillips et al, 2018).…”
mentioning
confidence: 99%
“…Giant dyke swarms are recognised worldwide onshore (e.g., Ernst and Youbi, 2017;Ernst, 2014;Bryan and Ernst, 2008;Coffin and Eldholm, 2005;Coffin and Eldholm, 1994;Bryan et al, 2010;Hou et al, 2010;Halls and Fahrig, 1987;Halls, 1982;Ernst and Baragar, 1992). Projection of these onshore dyke swarms and the known importance of dyking to break-up and formation of magma-rich margins suggests dyke swarms should also be prevalent on offshore continental shelves (see Magee et al, 2019 and references therein). Our work extends a growing consensus that vertical dykes can be recognised in seismic reflection data imaging continental margins (e.g., Wall et al, 2010;Bosworth et al, 2015;Malehmir et al, 2018;Holford et al, 2017;Kirton and Donato, 1985;Ardakani et al, 2017;Jaunich, 1983;Plazibat et al, 2019).…”
Section: Implications and Future Studiesmentioning
confidence: 99%
“…In particular, Phillips et al (2018) demonstrated the width of a dyke swarm imaged offshore southern Norway increased with depth, implying the plan-view morphology of a dyke swarm may not be a proxy for its 3D geometry (or total volume); i.e. the plan-view morphology of a dyke swarm is a function of its attitude relative to the present topography (see also Magee et al, 2019). We can use different physical, analytical, and numerical modelling approaches to evaluate the 3D geometry of dyke swarms, and to establish how their structure can be inferred from principally 2D, surfacebased analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(e.g., Macdonald et al, 1988;Jolly and Sanderson, 1995;Paquet et al, 2007;Bunger et al, 2013). Advancing our understanding of dyke swarm emplacement thus requires a method for imaging their 3D structure in detail (e.g., Magee et al, 2018;Phillips et al, 2018;Magee et al, 2019).…”
mentioning
confidence: 99%